Cryopreservation of ram semen: baicalein efficiency on oxidative stress, chromatin integrity, viability and motility post thaw - Avdatek, Fatih; Güngör, Şükrü; Gülhan, Mehmet Fuat; İnanç, Muhammed Enes and Olğaç, Kemal Tuna and Denk, Barış and Yeni, Deniz and Taşdemir, Umut (Frontiers in Veterinary Science, 2024)
Baicalein (B) has potential antioxidant properties, but it has not been tested as a ram semen extender. This study aimed to assess the impact of B on various semen parameters and determine its potential influence on semen quality after the freeze-thawing process. During the breeding season, ejaculates were obtained from four rams with the aid of an artificial vagina. The collected mixed sperm semen samples were divided into four groups: control (C; 0), B0.5 (0.5 mM), B1 (1 mM), and B2 (2 mM). After semen extension, the samples were loaded into 0.25 mL straws and stored for 2 hours at 4°C prior to freezing in liquid nitrogen vapor and thawed in a water bath at 37°C. Among the groups, B0.5 demonstrated the highest progressive motility results, while B1 and B2 exhibited reduced motility (p<0.05). In terms of high mitochondrial membrane potential, plasma membrane and acrosome integrity, and viability, B0.5 showed significantly superior outcomes to the other B groups (p<0.05), although it was not significantly better than C. B1 displayed the highest plasma membrane integrity levels (p<0.05). Notably, B2 displayed the lowest total antioxidant status levels among the groups (p<0.05). The findings of this study suggested that the in vitro spermatological characteristics of ram spermatozoa such as progressive motility and chromatin integrity can be protected from the freeze-thawing process by using the 0.5 mM dose of baicalein as a semen extender. The treatment of sperm freezing might benefit from further in-depth research on the role of B in the improvement of cryoinjury and its underlying processes.